Potential Role of Peptidylarginine Deiminase Enzymes and Protein Citrullination in Cancer Pathogenesis - Sunish Mohanan; Brian D. Cherrington; Sachi Horibata; John L. McElwee; Paul R. Thompson; Scott A. Coonrod (Biochemistry Research International)
The peptidylarginine deiminases (PADs) are a family of posttranslational modification enzymes that catalyze the conversion of positively charged protein-bound arginine and methylarginine residues to the uncharged, nonstandard amino acid citrulline. This enzymatic activity is referred to as citrullination or, alternatively, deimination. Citrullination can significantly affect biochemical pathways by altering the structure and function of target proteins. Five mammalian PAD family members (PADs 1–4 and 6) have been described and show tissue-specific distribution. Recent reviews on PADs have focused on their role in autoimmune diseases. Here, we will discuss the potential role of PADs in tumor progression and tumor-associated inflammation. In the context of cancer, increasing clinical evidence suggests that PAD4 (and possibly PAD2) has important roles in tumor progression. The link between PADs and cancer is strengthened by recent findings showing that treatment of cell lines and mice with PAD inhibitors significantly suppresses tumor growth and, interestingly, inflammatory symptoms. At the molecular level, transcription factors, coregulators, and histones are functional targets for citrullination by PADs, and citrullination of these targets can affect gene expression in multiple tumor cell lines. Next generation isozyme-specific PAD inhibitors may have therapeutic potential to regulate both the inflammatory tumor microenvironment and tumor cell growth.